Wittgenstein's language games as a theory of learning disabilities - Timmons, Stephen (Nursing philosophy, 2006)
Sociological approaches to the understanding of learning disabilities are perhaps not as fully developed as they might be. Wittgenstein's notion of the language game is elucidated, and its relevance to the analysis of learning disabilities as a social phenomenon is explained. This gives some insight into an alternative conception of what learning disabilities might be, and why people who are classified as having learning disabilities continue, to some extent, to be excluded from full participation in society.